DURASI PEMBELAJARAN DAN DAMPAKNYA: Studi Kasus Pembelajaran Desain Layout - Widyatmoko, FX. ‘Koskow’ (SNADES, 2025)
This article is the result of reviewing practical learning, especially the duration of learning. Generally, face-to-face lectures are held once a week, and twice a week, especially for courses with high credits. The habit of meeting duration is to be reviewed. The goal is to find a learning model that is more adequate to the current situation. The author’s efforts in reviewing came from learning the elective course Layout Design. From the review, several aspects were found that became basic insights in future learning such as the nature of knowledge, skills, how knowledge is created by learning, the creative side in constructing independent knowledge by students, the level of complexity of materials and works. The result is an offer in redesigning the duration of learning that is different from what has been commonly applied so far. Compliance with the sub-theme "Design and Creativity for Quality Education" namely in terms of the accuracy of learning methods, setting the duration of learning and the form of assignments that invite each student to build their own knowledge that they will learn. The various aspects above begin with manual practical learning and end with digital practical learning. In short, evaluating and offering new habits for quality visual communication design education that is based on experience supported by learning theory and perspectives from observers of visual communication design education.